Are workspaces gender neutral? A literature review and a research agenda. Issue 8 (17th November 2022) - Migliore, Alessandra; Rossi-Lamastra, Cristina; Tagliaro, Chiara
ABSTRACT: This study undertakes a systematic literature review (SLR) on how the workspace influences female workers and, more generally, gender equality. Within the broader context of Diversity, Equity and Inclusion (DE&I) matters, gender issues have attracted ample attention from scholars and policymakers. However, research on the specific topic of this SLR is sparse and fragmented, especially for what concerns the implications on workplace design and management. This paper systematizes the actual knowledge on the subject by reviewing 68 articles published in the last 10 years. Authors critically analyze these articles according to two vital spatial elements: workspace typologies and workspace interiors . The reviewed articles document a general convincement shared by different scientific fields that the workspace affects women and men differently. The results show that space is a crucial element for enhancing gender equality in the workplace. Although the reviewed articles cover multiple disciplines, an interdisciplinary approach is still missing. The concluding section proposes a future research agenda, novel theoretical approaches and methodological advancements, while highlighting practical implications.